Missouri Public School Teachers' Perception of Tenure - Roache, Roberta Savone (Lindenwood University, 2015)
In the state of Missouri, 550 public school superintendents were selected to have their district teachers participate in a study to provide information regarding the perception of teacher tenure. Approximately 64,000 PreK-12 public school teachers in Missouri were sent an 18 question online survey designed by the researcher to assess Missouri public school teachers’ perception of teacher tenure. A sample of 497 Missouri teachers participated in this study. Sub-questions of the purpose of the research study were adapted from Kersten (2006): (1) When teachers achieve tenure, are they more effective and highly qualified? (2) If teacher tenure was eliminated, would student achievement increase? (3) Does the teacher tenure law in Missouri protect good teachers from arbitrary dismissal? and (4) Do teachers have knowledge of the proposed revised tenure law in Missouri? The respondents were prompted to identify gender, years in current position, education level, description of grade levels in school building, and school district’s region. The research study findings produced several conclusions which included the following: (1) Teacher tenure in Missouri does not determine if teachers are effective and highly qualified; (2) Abolishing tenure or changing the current tenure law will not improve student achievement; (3) Tenure is perceived to protect competent teachers from arbitrary dismissal; however, incompetent or ineffective teachers are seldom dismissed; and (4) Many teachers have knowledge of the proposed revised teacher tenure law in Missouri, and they learned of the upcoming legislation from professional teaching organizations.